Pendampingan Penyusunan Administrasi Usaha Peningkatan Pendapatan Keluarga (UP2K) Tim Penggerak Pemberdayaan KeseSjahteraan Keluarga (TP PKK) Desa Tegalrejo Ceper Klaten - Isnaini Lilis Elviyanti; Ahmad Aftah Syukron; Titi Maemunah; Dwiyono Waluyo (Jurnal Pengabdian Masyarakat Nusantara, 2024)
The family income improvement business group (UP2K) is one of the Work Programs (POKJA) II of the Village PKK Team to help increase family income. In order for the UP2K program to run properly and correctly, it is necessary to have good and correct administrative bookkeeping as well. As well as professional and trustworthy managers are also the main capital for UP2K development. Therefore, there has been assistance in the preparation of administrative bookkeeping UP2K TP. PKK Tegalrejo Ceper Klaten Village so that the UP2K program Tegalrejo Ceper Klaten Village can develop for the better. This administrative bookkeeping assistance was given to the Special Group (Poksus) UP2K POKJA II TP. PKK Tegalrejo Ceper Klaten Village. This assistance is in the form of training in the preparation of UP2K administration books. The Tegalrejo Ceper Klaten Village Government hopes that UP2K will be more developed and professionally managed. The existence of the UP2K program in Tegalrejo Ceper Klaten Village is expected to increase the development of family economic businesses in Tegalrejo Ceper Klaten Village.